2011
DOI: 10.3989/gya.033210
|View full text |Cite
|
Sign up to set email alerts
|

Some Biological Compounds, Radical Scavenging Capacities and Antimicrobial Activities in the seeds of <i>Nepeta italica</i> L. and <i>Sideritis montana</i> L. subsp. <i>montana</i> from Turkey

Abstract: RESUMENCompuestos biológicos, capacidad atrapadora de radicales libres y actividad antimicrobiana de las semillas de Nepeta italica L. y Sideritis montana L. subsp. montana de Turquía.Este estudio ha determinado algunos compuestos bioló-gicos (ácidos grasos, vitaminas liposolubles, esteroles y flavonoides), capacidad atrapadora de radicales libres, y actividades antimicrobianas de las semillas de Nepeta italica L. y Sideritis montana L. subsp. montana. Se encontró que el áci-do palmítico (C16:0; 8.54±0.13-3.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The methanol extracts of Z clinopodioides and N italica demonstrated activity only against M smegmatis (23 and 291 μg/mL, respectively). Previous studies showed that the seeds of N italica exhibit significant antimicrobial activity 46 . As demonstrated in the previous report, the ethanol extract of Z clinopodioides exhibited good antibacterial activity against Staphylococcus aureus , Staphylococcus epidermidis , Bacillus cereus and Pseudomonasa eruginosa with a high MIC value of 14.5 μg/mL, respectively 47 .…”
Section: Resultsmentioning
confidence: 66%
“…The methanol extracts of Z clinopodioides and N italica demonstrated activity only against M smegmatis (23 and 291 μg/mL, respectively). Previous studies showed that the seeds of N italica exhibit significant antimicrobial activity 46 . As demonstrated in the previous report, the ethanol extract of Z clinopodioides exhibited good antibacterial activity against Staphylococcus aureus , Staphylococcus epidermidis , Bacillus cereus and Pseudomonasa eruginosa with a high MIC value of 14.5 μg/mL, respectively 47 .…”
Section: Resultsmentioning
confidence: 66%
“…Palmitic acid (14.34%) and oleic acid (13.14%) in S. libanotica ssp. linearis ; capric acid (42.72%) and steric acid (30.64%) in S. taurica ; linolenic acid (77.04 ± 2.07%) and oleic acid (18.83 ± 0.10%) in S. montana were determined as major fatty acids (Aboutabl et al, ; Demirtas et al, ; Emre, Kurşat, & Yılmaz, ).…”
Section: Resultsmentioning
confidence: 99%
“…Lipid-soluble vitamins were extracted from the lipid fraction according to the method of Emre [19]. e extracted lipids of seed material were dissolved in acetonitrile/methanol (75/25 v/v) and 50 mL were injected into the HPLC instrument (Shimadzu, Kyoto, Japan).…”
Section: Fatty Acid and Vitaminmentioning
confidence: 99%